Regional convergence in Portugal: the role of national (and EU) policies - Amorim, C. A.
In this study we assess the impact of a wide range of Portuguese domestic policies on cohesion in Portugal´s seven NUTS II regions. We focus mainly on regional economic cohesion, although social cohesion effects are also considered. We also look at whether the Portuguese regions have been able to share equitably in the country´s overall growth or whether there have been asymmetries and divergences in their growth patterns. While the purpose of the study is to analyse the policy impact of Community policies in two regions for reference. This is important for the case of Portugal where structural operations have been substantial and where European Union and national efforts seem to be highly intertwined.